The Urgency of Arabic Language Learning Media in the Digital Age - Hasan Abidin; Sutrisno (STAI At-Tahdzib Rejoagung Ngoro Jombang, 2025)
This article discusses the urgency of using digital learning media in Arabic language teaching in the digital era, which has fundamentally changed the educational landscape and demands significant adaptations in learning methods and media. Arabic, as a language of religious, cultural, and global significance, faces unique challenges in its learning amidst the learning style preferences of a contemporary, technology-savvy generation. The study focuses on the impact of digital media, identifying its opportunities and challenges, and reviewing successful implementations at various levels of education. The study’s findings illustrate that digital learning media not only enhance motivation and accessibility but also personalize and enrich the Arabic language learning experience. Success depends heavily on a holistic implementation strategy, including teacher competency development, equitable infrastructure provision, and relevant content design. The study confirms that digital media is not merely a complementary tool but an essential component for ensuring the relevance and effectiveness of Arabic language learning in the future.